Sistem Keamanan Jaringan Komputer dan Data Dengan Menggunakan Metode Port Knocking - Riska, Putu; Sugiartawan, Putu; Wiratama, Ichsan (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2018)
Data and information security makes information technology must be updated at all times. Along with the ever-changing information technology development, making information security is very important. Many attacks carried out by irresponsible people to attack the server. These attacks are often performed on open ports, which in turn will allow unauthorized and unauthorized people to easily control ports that have been entered. So to do security on computer network in overcoming attack on ports, one of them is by using Port knoking method. In order to avoid attacks carried out in the open port state a Port knoking method is used and set parameters for this computer device to have no open communication ports to enter, but the device is still accessible from the outside. So as to make people who do not have access rights do not have the opportunity to enter the ports that exist.